Teaching entrepreneurship in undergraduate Nursing course: evaluation of an educational proposal - Rosana Maria Barreto Colichi; Wilza Carla Spiri; Carmen Maria Casquel Monti Juliani; Silvana Andrea Molina Lima (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To evaluate a proposal for teaching entrepreneurship in an undergraduate Nursing course that uses active methodologies and activities based on the theory of meaningful learning. Methods: Interventional, prospective study, with a quantitative perspective, with a total of 102 participating students, carried out from July 2017 to December 2019 at a public university in the state of Sao Paulo. Statistical analysis were performed by non-parametric Chi-square or Fisher's exact tests, with differences considered statistically significant if p < 0.05. Results: Improvements were observed in almost all items evaluated, revealing that meaningful learning became more effective with the use of active teaching methodologies. Most students need adaptation and effort to be put into these methods. Conclusions: The proposal offers pedagogical content adaptation, specifically for nursing students. New research should expand teaching-learning techniques for the development of future nurses, preparing them adequately for the job market.